The Influence of Work Motivation, Organizational Commitment and Organizational Culture on Employee Performance of Syariah Bank in Central Java - Edwin Zusrony; Dewi Widyaningsih; Heni Susilowati; Titin Hargyatni (Inovbiz: Jurnal Inovasi Bisnis, 2021)
The goal of this research is to investigate the effects of job motivation, organizational commitment, and organizational culture on the performance of Islamic bank employees. The scope of this research is limited to a single Islamic bank branch in Central Java. This is a quantitative study in which the data was collected using a questionnaire. The participants in this study were chosen from a population of 30 people using saturated sampling or census sampling methods, in which samples were taken from the entire community. SPSS 23 for Windows was used to analyze the data, which was done using multiple linear regression.  All independent variables have a positive and significant influence on sharia bank workers' performance factors, either partially or simultaneously, according to the study.